The Need to Integrate Themes of Environmental Education in the School Curriculum in Kenya - Kimiti, Richard Peter; Cheruto, Kipkoech Lydia (HRmars, 2013)
Globally, the environment is under pressure from climatic variability and anthropogenic activities including deforestation, wetland and water catchment destruction, agro-chemicals use and urbanization among others. The foregoing partly results from inappropriate information, ignorance, weak regulatory institutions and poverty, whose crosspollination exacerbates the fragility of the environment, threatening flora and fauna. The purpose of this study was therefore to investigate the need to establish the themes of environmental education integrated in the school curriculum, establish the strategies used to teach themes of environmental education in the school curriculum. This study adopted a descriptive survey design. The findings of the study revealed that the themes on environmental education were incorporated in the following subjects: geography, languages and religious education. The strategies used to teach environmental education included; lecture, field trips, discussions and guest speakers. It was therefore, concluded that the curriculum implementers should give more emphasis on themes of environmental education as a method of enhancing good management of the environment in Kenya.
Keywords: Curriculum; Development; Education; Environmental; Integration; Themes